Studies on the combined effects of constant temperature and relative humidity on progeny production and sex-ratio of Cheiloneurus pyrillae Mani, an egg parasitoid of Pyrilla perpusilla Walker. - Yadav, R. P.; Chaudhary, J. P. (Contributions to Entomology = Beiträge zur Entomologie, 1988)
The natural population of the sugarcane leaf hopper (Pyrilla perpusilla Walker), one of the major pest insects on sugarcane in India is regulated by a large complex of natural enemies, the egg parasitoid Cheiloneurus pyrillae Mani being one of them. Effects of controlled temperature and relative humidity on progeny production and sexratio of this egg parasitoid are discussed for the first time. This parasitoid is able to breed and develop over a wide range of relative humidity but it is very specific in its temperature requirements. Its breeding activities may increase or decrease depending upon the temperature. Lower and upper extremes of temperature within which this parasitoid could continue to breed were around 15 and 30°C, respectively. From the fertility point of view, a temperature between 20 and 25°C seems to be suitable for it but a temperature at 22.5 ± 1.5°C is preferred. Rearing of this parasitoid at 20 or 22.5 ± 1.5°C proved to be most advantageous for getting the maximum rate of parasitoid emergence. The relative proportion of females increases with the corresponding decrease in temperature from 30 to 17.5 ± 1.5°C, and at all the temperatures, the females outnumbered the males. Taking all the points into consideration, for better multiplication and development of C. pyrillae, a temperature around 22.5°C needs to be maintained, whereas the arrangements for maintaining the relative humidity may not be needed.